Literature Review: Hospital Service Quality During The COVID-19 Pandemic - Salvany Zahra; Inge Dhamanti (Universitas Nusa Cendana, 2022)
Service quality is an important component in hospital management during the COVID-19 pandemic. During this pandemic, the lack of health workers and resources needed by patients may affect the quality of health services in hospitals. This review aims to provide an overview of the hospital quality services during the COVID-19 pandemic. The method used was literature review. Articles were searched through Google Scholar, Science direct and Pubmed with the keywords